Anteseden Keputusan Pembelian Sepeda Motor Matic - Putra, I Wayan Mika Abdi; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the influence of brand image and lifestyle on purchasing decisions for Honda automatic motorbikes. This research was conducted at the Tirta Agung Motor Dealer in Denpasar. The population in this study is not known with certainty. The sample size determined was 102 respondents using purposive sampling technique. Data collection was carried out using a questionnaire which was measured using a Likert Scale with five answer choices. Hypothesis testing was carried out using multiple linear regression analysis. The analysis results prove that purchasing decisions will increase significantly when the brand image and lifestyle get better.